FEATURES OF MATHEMATICAL DEVELOPMENT IN PRESCHOOL CHILDREN - Toshmatova Zamira Jumanovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Features of the formation of the concepts of numbers, quantities, numbers, forms, measure in preschool children are considered. Thus, recommendations were made to compare the numbers within 10, to form the concepts of the whole and part.